Livestock-mediated nutrient transfers in Sahelian agro-ecosystems - Hiernaux, Pierre H.Y.; Fernández Rivera, S.; Schlecht, Eva; Turner, M.; Williams, Timothy O. (Margraf Verlag, 1997)
Night corralling of livestock directly in crop fields during the dry season contributes to nutrient cycling for the benefit of crops. Rangeland grazing and corralling livestock on selected croplands result in a spatial transfer of organic matter and nutrients from rangelands to the corralling sites. These transfers were measured over a year in three villages of Niger that differ in densities of human and livestock populations and proportion of land that is cropped. In each land unit, nutrient transfers were calculated as the difference between forage intake and excretions. Forage intake by livestock accounted for only 11 to 19 percent of the annual herbage yield of rangelands and 7 to 10 percent of weeds and millet crop residues. Through faecal excretion, livestock recycled 50 percent of organic matter, 48 percent of nitrogen and 85 percent of phosphorus intake. Livestock management led to a manure concentration on selected fields that received 5 to 13 times more manure than average village land. Despite moderate annual stocking rates, 7 to 12 TLU Km-2 (Tropical Livestock Unit = 250 kg live weight), grazing pressure in early wet season reached 68 to 160 TLU d t-1 of forage leading to deterimental effects on rangeland productivity and species composition.